A relational framework for smart information delivery manual (IDM) specifications. (August 2021) - Jeon, Kahyun; Lee, Ghang; Kang, Seoungwoo; Roh, Hyunsung; Jung, Jeaeun; Lee, Kyungha; Baldwin, Mark
Highlights: A relational framework for the smart information delivery manual (IDM) is proposed. The framework is a translation of ISO 29481-1 (IDM) into a machine-readable format. The IDM is defined as the relation that interlinks IDM components. The relation between the use case and the IDM is formally defined. The explicit cardinalities between IDM components are identified and specified. Abstract: This study proposes a relational framework for standardized machine-applicable, readable, and transferable (smart) information delivery manual (IDM) specifications. As the demand for projects using building information modeling (BIM) increases, there is a more acute awareness and need for clearly defined information requirements to support the BIM projects. The ISO 29481-1 IDM standard defines how to specify exchange requirements (ERs) and their use cases (UCs) using a process map (PM). However, IDM specifications are currently not easily sharable or reusable due to the lack of a commonly accepted standard data schema. This study overcomes this problem by identifying definitions and relationships of IDM components to develop the relational framework for an IDM data schema. An extensive review of existing IDM-related documents and standards, and iterative international meetings, were conducted by 46 international IDM experts from 16 countries. A consensus on the relational framework was then reached through three Delphi survey rounds. The formalized relational IDM framework lays a foundation for further developing an IDM data schema as an international standard.